Assessing Recount Text Writing Ability Through Dicto-Comp of the Twelfth Grade Students of SMK Kharisma Mengwi in Academic Year 2015/2016 - Wipradnyana, Gede (Yavana Bhasha : Journal of English Language Education, 2018)
Writing is an activity which is used to express our ideas, emotions, thoughts and transfer them onto written form. In addition, teaching and assessment are inseparable in teaching and learning process. However, there are many problems confronted by the teachers in assessing the students’ writing ability; furthermore, assessment has become a problem in teaching and learning process. The undertaking of the present study dealt with assessing recount text writing ability of the twelfth-grade students of SMK Kharisma Mengwi in academic year 2015/2016 through dicto-comp. The present study made use of ex post facto research design with descriptive analysis. The data required for the present study were gathered by means of administering dicto-comp to 40 samples of this study which were determined through random sampling technique with lottery system. The obtained data were analyzed using norm reference measure of five standard values. To sum up, these research findings revealed that there were 67.50% of the samples under study succeeded and the others 32.50% failed in writing recount text which was assessed by using dicto-comp. Keywords: assessing, recount text writing ability and dicto-comp.